THE EXPERIENCE OF PATIENTS WITH HEAD AND NECK CANCER REGARDING SELF-CARE FOR RADIODERMATITIS - Oliveira, Sandra Suely Silva de; Sagica, Tais dos Passos; Vilhena, Débora Igreja de; Moreira, Bruna Camila Blans; Silva, Marcos José Risuenho Brito; Sousa, Maiza Silva de; Santana, Mary Elizabeth de (Cogitare Enfermagem, 2024)
Objective: To analyze the experience of patients with head and neck cancer regarding self-care for radiodermatitis associated with sociodemographic and clinical-pathological factors. Method: A descriptive study with a qualitative approach, carried out at a High Complexity Oncology Reference Center in Belém - Pará - Brazil. It was conducted through interviews and analysis of medical records. The data were collected from February to April 2022 and processed using Bardin’s content analysis supported by the IRAMUTEQ software. Results: Three subcategories emerged: The importance of the patient’s knowledge about radiotherapy; Identification of adverse effects related to the treatment; and Nurses’ guidance on self-care. Final Considerations: The patients’ knowledge about the treatment was incipient, adverse effects were identified by the negative impact on their self-esteem and self-image, and self-care guidance was effective in reproducing care. The study provides an opportunity to develop an appropriate teaching strategy in future research.